Penerapan Model Pembelajaran Berbasis Proyek (Project Based Learning) untuk Meningkatkan Pemahaman Konsep Keragaman Budaya Indonesia - Syamsur Rizal (Jurnal Ilmu Pendidikan, 2025)
Students’ understanding of the concept of cultural diversity in Indonesia remains relatively low due to the dominance of conventional teaching methods that lack student engagement. To address this issue, this study aimed to apply the Project-Based Learning (PjBL) model to enhance fourth-grade students’ conceptual understanding of Indonesian cultural diversity at SDN 2 Mamben Daya. The study employed a qualitative approach using Classroom Action Research (CAR) with the Kemmis and McTaggart model, conducted over two cycles from July to December 2024. The research subjects consisted of 25 students, including 16 boys and 9 girls. Data collection instruments included observation, interviews, documentation, and concept understanding tests, which were analyzed both qualitatively and quantitatively. The findings revealed a significant improvement across all observed aspects. The observation scores of student activity increased from 68 in cycle I to 86 in cycle II. Interview scores improved from 3.2 to 4.5, documentation scores rose from 3.5 to 4.7, and concept understanding test scores increased from an average of 70 to 85. These results indicate that the project-based learning model fosters active student engagement and enhances their conceptual grasp of cultural diversity in Indonesia. In conclusion, the implementation of the project-based learning model effectively enhances students’ cognitive, affective, and psychomotor skills. This model is a viable alternative teaching strategy for elementary thematic learning, particularly for subjects requiring exploration and active student involvement.